ASSOCIATION OF CYCLING BETWEEN ANTI-TNFS VERSUS SWITCHING TO USTEKINUMAB WITH MEDICATION PERSISTENCE IN ANTI-TNF EXPERIENCED PATIENTS WITH CROHN'S DISEASE. (26th January 2023) - Zhdanava, Maryia; Ding, Zhijie; Manceur, Ameur; Zhao, Ruizhi; Holiday, Christopher; Godwin, Bridget; Pilon, Dominic; Kachroo, Sumesh
Abstract: BACKGROUND: Anti-tumor necrosis factor inhibitors (anti-TNFs) are biologics commonly used for the treatment of Crohn's disease (CD). Over time, patients may require adjustment to anti-TNF therapy, including cycling to a different anti-TNF or switching to a biologic with an alternate mechanism of action. Choice of a treatment strategy could be key to managing symptoms on a sustained basis. This study aimed to compare real-world persistence among patients with CD who cycled to another anti-TNF agent or switched to ustekinumab. METHODS: Adults with CD treated with an anti-TNF, whose first switching to ustekinumab or cycling to a new anti-TNF (index date) occurred between 09/23/2016 and 08/01/2019 were selected from the IBM® MarketScan® Commercial Database. Patients had ≥12 months of continuous insurance eligibility before the initiation of the first anti-TNF, discontinued the first anti-TNF within 12 months before the index date (baseline), and had no other immune disorders during baseline. Cohorts were balanced on baseline characteristics using inverse probability of treatment weights. Persistence on index biologic (ustekinumab or a new anti-TNF) was defined as absence of therapy exposure gaps >120 days (ustekinumab, infliximab) or >60 days (adalimumab, certolizumab) between days of supply. Composite endpoints were persistence while on monotherapy (no immunomodulators/non-index biologics), and persistence and being corticosteroid-free (no corticosteroids with ≥14 days of supply after day 90 post-index). Weighted Kaplan-Meier and Cox models were used to assess outcomes at 12 months post-index. RESULTS: The weighted sample included 325 patients in the ustekinumab cohort and 328 in the cycling cohort (Fig. 1 ). At 12 months post-index, 76.6% versus 67.5% persisted on the index biologic in the ustekinumab versus the cycling cohort (Fig. 2a ); the rate of persistence was 47% higher in the ustekinumab cohort (hazard ratio [HR]: 1.47; 95% confidence interval [CI]: 1.08-2.01; p-value 0.0158). Moreover, 61.6% versus 44.1% persisted on the index biologic while on monotherapy, respectively (Fig. 2b ); the rate of persistence while on monotherapy was 68% higher in the ustekinumab cohort (HR: 1.68; 95% CI: 1.33-2.13; p-value <0.001). Finally, 54.8% vs 50.2% were persistent and corticosteroid-free, respectively (Fig. 2c ); the rate of being persistent and corticosteroid free numerically trended 9% higher in the ustekinumab cohort but statistical significance was not reached (HR: 1.09; 95% CI: 0.87-1.38; p-value 0.4527). CONCLUSIONS: After discontinuation of the first anti-TNF, persistence on therapy was better among patients with CD who switched to ustekinumab compared to those who cycled to a new anti-TNF. These findings may inform treatment strategies for patients on the first anti-TNF agent who require treatment adjustment.